Facile fabrication of graphene oxide-polyethylenimine composite and its application for the Cr(VI) removal. Issue 15 (13th October 2018) - Feng, Xuezhen; Liang, Chunyan; Yu, Jingang; Jiang, Xinyu
ABSTRACT: A binary composite consisting of graphene oxide (GO) and polyethylenimine (PEI) was fabricated by a facile physical mixing. Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscope (FE-SEM), thermo-gravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) and Zeta potential were used to characterize the prepared graphene oxide-polyethylenimine composite (GOPC). A series of experiments were carried out to investigate the effects of some important parameters, such as molecular weight of PEI, pH, time and temperature, on the adsorption efficiency of GOPC. Due to the high amine density of GOPC, its adsorption for Cr(VI) occurred more easily at lower pH mainly via electrostatic interaction. The adsorption process matched well with the Langmuir isotherm model and the pseudo-second-order kinetic model. The maximum adsorption capacity from the Langmuir model was 370.37 mg/g at pH 2.0 and 45°C for GOPC. Thermodynamic parameters revealed spontaneous and endothermic nature of the Cr(VI) adsorption onto GOPC. The main adsorption mechanism of GOPC toward Cr(VI) was electrostatic interaction. The adsorption-desorption experiments suggested GOPC was easily recycled and its stable adsorption capacity endowed it great potential as an adsorbent of Cr(VI) from wastewater.